DESAIN LABEL DAN MEDIA PROMOSI BAGI DAYA TARIK UMKM PRODUK KERIPIK - Angelica Lokollo; Dian Utami Sutiksno (P3M Politeknik Negeri Ambon, 2025)
This study aims to design packaging labels and apply promotions for social media-based marketing for chip products. MSMEs engaged in the culinary sector are chip product businesses located at Waipirit Port, Kairatu District, West Seram Regency. So far, in the sale of chip products, there are still several things that are considered lacking, especially those related to the product label for chips on the packaging and digital-based marketing.These chip products do not have labels and some already have labels but are not optimal and have not utilized digital media to promote their products such as; Facebook, WhatsApp, Instagram, etc. as a means to market their products, so that the sales process is only carried out directly at the place they are occupying as their place of sale. The design of product labels in this study was carried out using the VIEW analysis technique and the theory of product label design. Creating social media accounts as a marketing medium to introduce chip products to a wider market. The results of the new product label design when applied to chip products can improve the image of the product highlighted on the product packaging, look more attractive, can also be a dissector with similar products and have the opportunity to enter modern markets. With a combination of social media accounts, it can expand the product marketing area, promote products and facilitate communication between producers and consumers to increase attractiveness.